Endovascular treatment for stroke due to occlusion of medium or distal vessels - Psychogios, Marios-Nikos; Brehm, Alex; Ribo, Marc; Rizzo, Federica; Strbian, Daniel; Räty, Silja; Arenillas, Juan F.; Martínez-Galdámez, Mario; Hajdu, Steven D.; Michel, Patrik; Gralla, Jan; Piechowiak, Eike I.; et al. (The New England journal of medicine, 2025)
In this trial involving 543 patients with stroke due to occlusion of medium or distal vessels, endovascular treatment within 24 hours after the onset of symptoms was not effective in improving functional outcome at 90 days.